O nazismo vai ao cinema: construção identitária na obra de Leni Riefenstahl - Frigeri, Renata Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Esta pesquisa visa investigar como Leni Riefenstahl usou o cinema, um instrumento da modernidade, para explorar elementos pertencentes ao romantismo histórico presentes no Zeitgeist, o “espírito do tempo”, e assim redefinir a identidade ariana em sua obra cinematográfica, como almejada por Adolf Hitler. As quatro produções selecionadas para análise são A Luz Azul (Das blaue Licht, 1932), O Triunfo da Vontade (Triumph des Willens, 1935), Olympia (Idem, 1938) e Tiefland (Idem, 1954). Embora as películas contemplem temas distintos e tenham sido produzidas com um intervalo de 22 anos, elas possuem unicidade identária em seu cerne. Esta tese percorre os contextos histórico, político e cultural, respectivamente, por meio das obras de Richard Evans (2014), Ian Kershaw (2010), Peter Gay (1978), Siegfried Kracauer (1988) e Lotte Eisner (1985); os conceitos de cultura e identidade são adotados a partir da perspectiva de Denys Cuche (1999) e Clifford Geertz (2015). Para a análise das películas, elegeu-se como metodologia o esquema quaternário de Massimo Canevacci (1990) e a binariedade proposta por Claude Lévi-Strauss (2012 e 2013). Os filmes selecionados fornecem elementos que permitem aferir o espírito do tempo na Alemanha, assim como a ideologia da diretora, que mesmo após a queda do regime nazista manteve em sua obra elementos identitários alinhados com o propósito de Hitler.

This research seeks to investigate on how Leni Riefenstahl used a modernity instrument such as cinema, to explore elements of historical romanticism in Zeitgeist, the “spirit of time” and therefore redefine the Aryan identity in his cinematographic work, as longed by Adolf Hitler. Four productions were chosen for the analysis, including: The Blue Light (Das Blaue Licht, 1932), Triumph of the Will (Triumph des Willens, 1935), Olympia (Olympia, 1938) and Tiefland (Tiefland, 1954). Although the movies contemplate different themes and were produced with an intermission of 22 years, they share an identity oneness in their core. This present thesis travels through the historical, political and cultural contexts, respectively, by means of Richard Evans’ (2014), Ian Kershaw’s (2010), Peter Gay’s (1978), Siegfried Kracauer’s (1988) and Lotte Eisner’s (1985) works; the concepts of culture and identity are adopted from the perspective of Denys Cuche (1999) and Clifford Geertz (2015). For the movies’ analysis, the methodology chosen were the quaternary scheme by Massimo Canevacci (1990) and the binarity proposed by Claude Lévi-Strauss (2012 and 2013). The selected movies provide elements that allow assess to the spirit of time in Germany, as well as the directors’ ideology, that even after the fall of the Nazi regime she kept identity elements in her works, aligned with Hitler’s purpose.
Nazism in the cinema: identity construction in the works of Leni Riefenstahl
Keywords: Leni Riefenstahl; Cinema nazista; Identidade germânica; Zeitgeist nazista; Modernismo reacionário; Nazi cinema; Germanic identity; Nazi zeitgeist; Reactionary modernism